“East Indian cart”, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
Two men on cart led by a donkey, around the Queen’s Park Savannah, Port of Spain.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Donkeys--Trinidad and Tobago; Draft animals--Trinidad and Tobago; East Indians--Trinidad and Tobago; Men--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Queen's Park Savannah